Estudio de prefactibilidad para la instalación de una planta productora de chocolates con quinua (Chenopodium quinoa) y maca (Lepidium meyenii) - Ruiz Del Castillo, Pedro Augusto (2021)
The present project on the Preliminary Study for the installation of a production plant producing chocolates with quinoa (chenopodium quinoa) and maca (lepidium meyenii) requires an investment of S/. 2 760 657,53 and will generate a financial VAN of S/. 891 939,82, a financial TIR of 45%, with a COK of 21.56%, which shows that the project is profitable. The price of the product will be S /. 9.50 per unit (with IGV), the presentation will be in tablets of 80 grams and the sale through stores, supermarkets and self-services. The product is aimed at the inhabitants of Metropolitan Lima who belong to socioeconomic levels A and B, between the ages of 18 and 60 years. This target market determines a project demand of 190 543 chocolate bars during the first year, considering a 1.0% market share that will increase at a rate of 0.5% until obtaining 2% in the year 2024. Through a plant location analysis, it was defined that the most appropriate place to locate the company's facilities is the department of Lima, Lurín district. The required land size is 989 m2 and the plant size will be 450 474 units of chocolates, which is limited by market size. The production process has the following stages Cleaning, Stripping, Toasting, Grinding, Pressing, Mixing, Conching, Tempering, Molding and Refrigeration. In addition, the bottleneck is present in the mixing stage, in the mixer.